Uwagi na temat tzw. grobów rodzinnych kultury pomorskiej - Malinowski, Tadeusz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The paper argues against the concept that all graves of the Pomeranian culture with more than one urn should be regarded family burials. Such graves frequently resulted from storing cremated human bones to be buried during a single funeral service held for a number of deceased, as well as from putting remains of the same dead into various urns. At the same time a burial of a young woman and a newborn baby in separate urns could be termed a family burial.
Remarks on the so called family graves of the Pomeranian Culture